Effects of COVID-19 on the Liver and Mortality in Patients with SARS-CoV-2 Pneumonia Caused by Delta and Non-Delta Variants: An Analysis in a Single Centre - Monica Muntean; Violeta Briciu; Mihaela Lupse; Doina Colcear; Raul Vlad Macicasan; Agnes Csiszer; Alexandra Manole; Amanda Radulescu (MDPI AG, 2023)
The aim of this study was to ascertain patient characteristics, outcomes, and liver injuries in patients infected with different SARS-CoV-2 variants. Data from consecutive adult patients with severe/critical COVID-19 admitted to our hospital during the peak month of the Delta wave were compared to the ancestral, Alpha, and Omicron waves. The dataset of 551 hospitalized patients was similar in the Delta/non-Delta waves. At admission and discharge, the median aminotransferase levels were normal or slightly increased. During the Delta wave (172 vs. 379 non-Delta patients), more patients died (OR 1.69, 95%CI 1.09-2.56) or had liver injury at discharge (alanine aminotransferase, ALT ≥ 2 ULN) (OR 1.97, 95%CI 1.08-3.54). In-hospital mortality was associated with age, lung injury, intensive care unit admission, number of and cardiovascular comorbidities, diabetes, chronic kidney disease, and all inflammatory biomarkers. Serious liver injury at admission (ALT ≥ 5 × ULN) was significantly associated with in-hospital mortality (OR = 7.9, 95%CI 2-28.9). At discharge, drug-induced liver injury (DILI) was found in patients treated with remdesivir, ALT ≥ 2 ULN (OR = 2.62, 95%CI 1.22-5.75). Treatment with dexamethasone, remdesivir, and immunomodulators showed improved survival, OR = 0.50 (95%CI 0.33-0.77). Regardless of the variant and treatment options, less than 2% of patients displayed serious liver injury, which was not found to be a death predictor in multivariable analysis.